(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon the Master of the Messengers and the Seal of the Prophets, Abu al-Qasim Muhammad, and upon his good and pure household, and upon his chosen companions, who followed his guidance and were like his shadow, and upon those who followed them with kindness and followed their path until the Day of Judgment, and after... The issue of judiciary and judgment to resolve disputes has existed among people since ancient times. Even in primitive societies, there was a kind of arbitration to resolve disputes by the chief of the tribe or some of his relatives, or a person was appointed for this purpose. In fact, it is difficult to mention the date of the beginning of the judiciary except to say His age coincides with the age of human societies. I made this research an introduction, four topics and a conclusion, in which I talked about the three authorities in the Islamic government. In the first topic, I spoke about the legislative authority, its evidence and its importance.